The Influence of Commitment, Quality of Work, and Organizational Culture to Employee’s Achievement - beti nurbaiti; abu chanifah (Journal of Accounting, Business and Management (JABM), 2023)
ABSTRACT This research was conducted with the aim to study and analyze the Commitment, Quality of Work, and Organizational Culture of Employee Job Performance at the Secretariat of the Film Censorship Institution of the Ministry of Education and Culture. The population in this study were all employees of the Film Censorship Institution Secretariat and the sample used was 121 saturated newspaper reports. In conducting this research, the authors used a quantitative method using Structural Equation Modeling (SEM) with the help of Lisrel 8.8 software. and Annova. There is a significant difference and there is a positive difference between the variable Work Quality with Work Performance (t value> 1.96) and there is a significant difference but there is no difference between Organizational Culture and Work Performance variables (t value <1.96).